Emotions in Eden and after ancient jewish and christian perspectives on Genesis 2-4 - Crislip, Andrew T. 1973- (2019)
This article traces a long-lived tradition of understanding the Eden narrative and its aftermath as a story about the birth of painful emotions, what one might translate into English as shame, fear, and, above all, sadness. The consensus reading of Genesis in the Anglo-American tradition does not reflect an underlying emotional emphasis in the fateful oracle to Eve and Adam in Gen 3:16–17. Translations and commentaries overwhelmingly interpret God’s words as physiological and material, sentencing the woman to painful childbirth and the man to onerous labor in the fields. Yet, as demonstrated by a number of scholars, God’s oracle to the pair in the Hebrew text deals with pain more broadly, with a focus on emotional pain, especially sadness, sorrow, or grief. This emotional suffering is shared by man and woman, and is the catalyst for the first murder. Hellenistic Jewish and later Christian readers embraced and elaborated on this very early emotional aspect of the Eden myth. The Septuagint translates the oracle in unmistakably emotional terms, adopting vocabulary typical of popular moral philosophy, and clarifies the thematic connection between Genesis 3 and 4 by highlighting the emotional repercussions of the emotional change wrought by the primal transgression. Authors like Philo and Josephus interpreted the Eden narrative in fundamentally emotional ways, and pseudepigrapha were particularly engaged in drawing out and elaborating on the emotions of the Eden myth. Most of all the Greek Life of Adam and Eve and 4 Ezra transform the story into meditations on emotional suffering, the former retelling the myth, the latter repurposing it into an apocalyptic vision of joy and sorrow at the end times. Both texts furthermore identify sadness (lupē or tristitia, in Greek and Latin version of Gen 3:16–17) as dually significant, both as punishment and as a saving, divinizing quality, one which can also effect communion between human and divine. This way of reading Eden’s emotions dominated Christian reception of the Eden myth, from the Gospel of John on. Ptolemy, Didymus, Ambrose, Augustine, and others understood the Eden myth as primarily about the origin and meaning of emotional suffering. This style of reception remained a widespread reading until the turn of the twentieth century, when, for a variety of reasons, Christians began to read the oracle in the physiological and materialist terms (pain in childbirth and agricultural labor) that are now dominant.
Keywords: Genesis; Emotions; Hellenistic Judaism; Patristics; Gender